Occurrence, identification and phylogenetic analyses of cereal cyst nematodes in Kyrgyzstan - Saleh, Azzam; Yıldız, Senol; Özer, Göksel; Mokrini, Fouad; Tair Esenali Uulu; İmren, Mustafa; Dababat, Abdelfattah A. (Russian Society of Nematologists, 2023)
The study investigated the status of cereal cyst nematodes (CCN) in the main wheat-growing areas of Kyrgyzstan in 2020. Soil samples were taken from 69 different wheat fields located in Chuy and Issyk-Kul provinces. CCN were found in thirty-one out of the sixty-nine locations surveyed. The highest occurrence of CCN was in the Tyup location in Issyk-Kul province with 81 cysts (250 cm3 soil)–1 . The CCN populations were identified by both morphological and molecular analyses. According to the results, all populations were identified as Heterodera filipjevi. No variations in rDNA-ITS sequencing data were detected among the 31 cyst nematode populations, and the phylogenetic tree showed that Kyrgyz populations clustered with H. filipjevi populations from Belgium, Spain and Turkey, and separated populations from Germany, Iran, UK, Tajikistan, France and Russia. Therefore, the findings suggested the presence of only one species of CCN in the study areas of Kyrgyzstan, currently.